Reducing Cognitive Load and Improving Warfighter Problem Solving With Intelligent Virtual Assistants - de Melo, Celso M.; Kim, Kangsoo; Norouzi, Nahal; Bruder, Gerd; Welch, Gregory (Frontiers in Psychology, 2020)
Recent times have seen increasing interest in conversational assistants (e.g., Amazon Alexa) designed to help users in their daily tasks. In military settings, it is critical to design assistants that are, simultaneously, helpful and able to minimize the user’s cognitive load. Here we show that embodiment plays a key role in achieving that goal. We present an experiment where participants engaged in the desert survival task in augmented reality. Participants were paired with a voice assistant, an embodied assistant, or no assistant. The assistants made suggestions verbally throughout the task, whereas the embodied assistant further used gestures and emotion to communicate with the user. Our results indicate that both assistant conditions led to higher performance over the no assistant condition, but the embodied assistant achieved this with less cognitive burden on the decision maker than the non-embodied assistant. We discuss implications for the design of intelligent collaborative systems for the warfighter.